KOMPRESI CITRA MEDIS MENGGUNAKAN DISCRETE WAVELET TRANSFORM (DWT) DAN EMBEDDED ZEROTREE WAVELET - Anwar, Khairil (MATEMATIKA, 2008)
Medical image usually have a large sizely, this might be a problem when saving and sending, so compression of medical image are needed. One of method of compression is using DWT and EZW. Discrete Wavelet Transform (DWT) can compact the energy of image into a small number of coefficient, give combination information of frequency and time, so that more accurate to reconstruct of image.Â Embedded Zerotree Wavelet (EZW) is very effective for the quantization of discrete wavelet coefficients, can generate the bits in the bit stream in order of importance, yielding a fully embedded code, so that reacing maximal compression. From examination, can be concluded that compression at image of grayscale and RGB with different type of wavelet and level dekomposisi, resultÂ reasonable compression, because from all compression image yielded have value of PSNR > 40 dB. Â